Growth performance of Eastern European economies and comparable Western European countries - Balassa, B. Bertrand (American Economic Review, 1970)
A comparison of the industrial growth performances of the centrally planned economies of Eastern Europe with those of the decentralized Western European economies at comparable levels of development provides estimates of total and net factor productivity of the countries between 1953 and 1965. The measurement of total factor productivity reflects the assumptions of constant returns to scale and unchanged factor qualities over time. These assumptions are not fulfilled in practice; indeed, the results indicate the existence of a positive correlation between the growth factor inputs and total factor productivity. Adjusting for the effects of the former on the latter, estimates of the net factor productivity can be obtained. As this adjustment favors countries with a relatively low rate of growth of factor inputs in manufacturing, the relative positions of Norway, Ireland, and Czechoslovakia improve, while Bulgaria, Spain, and Yugoslavia rank lower. If adjustments are made to account for the indirect effects of the growth of factor inputs, differences in the growth performance of countries at lower and at higher levels of development are reduced. Economic and statistical data are included. 5 references.